2006
DOI: 10.1111/j.1742-7843.2006.pto_288.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromium Picolinate on Modified Forced Swimming Test in Diabetic Rats: Involvement of Serotonergic Pathways and Potassium Channels

Abstract: Depression occurs frequently in patients with diabetes mellitus. Chromium picolinate, an essential trace element is recommended for diabetes and also has been reported to benefit depression, but its mechanism is still debated. To investigate the mechanism, we studied its effects on serum insulin, serum glucose and on modified forced swimming test, a behavioural paradigm for depression in rats. The study involving co-administration of subactive doses of glimepiride, a K π channel blocker and chromium picolinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The translocation of glucose transporter 4 is mediated through insulin-independent phosphorylation and activation of AMPK [9]. In addition, recent studies [10,11] reported chromium action was absent in methyl-β-cyclodextrin-pretreated cells already displaying reduced plasma membrane cholesterol and increased glucose transporter 4 translocation, and these findings at the cell level are consistent with in vivo observations of improved glucose tolerance and decreased circulating cholesterol levels after chromium supplementation and serotonergic pathway involvement [12]. Early reports suggested that chromium enhances insulin binding, insulin receptor number, insulin internalization, and beta-cell sensitivity [13].…”
Section: Introductionsupporting
confidence: 75%
“…The translocation of glucose transporter 4 is mediated through insulin-independent phosphorylation and activation of AMPK [9]. In addition, recent studies [10,11] reported chromium action was absent in methyl-β-cyclodextrin-pretreated cells already displaying reduced plasma membrane cholesterol and increased glucose transporter 4 translocation, and these findings at the cell level are consistent with in vivo observations of improved glucose tolerance and decreased circulating cholesterol levels after chromium supplementation and serotonergic pathway involvement [12]. Early reports suggested that chromium enhances insulin binding, insulin receptor number, insulin internalization, and beta-cell sensitivity [13].…”
Section: Introductionsupporting
confidence: 75%
“…In experiments involving animals, however, it is impossible to examine directly the level of depression, but some behavioral features can be attributed to central nervous system activity. Hippocampal-dependent learning such as acquisition of spatial memory, long-term memory, and long-term spatial memory can be evaluated by various tests [21,23,63]. Diabetes-induced rats overcame a behavioral paradigm upon forced swimming test as reflected by increased percentage preference to open arm in elevated plus maze spontaneous alternation behavior paradigm as a measure of anxiety and memory [64,65] due to anxiolytic action of Cr through noradrenergic and serotonergic pathway [66].…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in tryptophan, 5-HT, melatonin, and noradrenaline were noted after sub-chronic dosing with chromium picolinate in a study by Franklin and Odontiadis [15]. Other studies have indicated that Cr(pic) 3 may be effective at alleviating symptoms of depression in individuals with metabolic disorders, presumably by enhancing insulin function, without the side effects typically associated with more traditional treatments, such as monoamine oxidase inhibitors [13,[16][17][18][19]. However, the clinical studies with Cr(pic) 3 [16,17,19] utilized very limited subject pools and require larger trials to firmly establish whether the supplement can beneficially affect atypical depression.…”
Section: Introductionmentioning
confidence: 98%